Patriarchy at the Pink Palace: Gender and Work Inside the Ontario Legislature - Coulter, Kendra (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
This article offers an anthropological analysis of the gender politics inside Queen's Park, Ontario’s provincial legislature. Using ethnographic data, I explore how political actors reproduce larger social and historical patterns of structural sexism and inequitable distributions of power, while simultaneously producing a localized political culture of inequity inside the legislature.